The Review and Critique of “Modern Political Analysis” - Mahdi Fadaei Mehrabani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Robert Dahl, as we know, is one of the political scientists who has a scientific approach to politics and political science and seeks to present politics as a science. In his book "Modern Political Analysis", he outlines his main positions on the concept of politics and how to analyze politics. The book, on the one hand, belongs to the power-oriented tradition of politics and, on the other hand, replaces a different concept of "influence" with the concept of power, claiming to have provided a scientific method for studying and looking at politics as well as a scientific model for practical policy and policy making. In this article, we will review the strengths and weaknesses of this book. This article contains some general critiques, including a critique of the book's scientist approach, its emphasis on influence as the main concept of politics, what modern political analysis is, and the consequences of this view of politics.